ANALISIS TERHADAP DELIK PERMUFAKATAN JAHAT PENDANAAN TERORISME DALAM PUTUSAN PENGADILAN NEGERI JAKARTA TIMUR NOMOR 398/PID/SUS/2018/PN.JKT.TIM - Richard Janwardo; Ade Adhari (Jurnal Hukum Adigama, 2022)
From a criminal law perspective, terrorism is a unique crime. The essence of terrorist acts isfunding and applies to all terrorist acts. Law Number 9 of 2013 concerning the Prevention andEradication of the Crime of Financing Terrorism regulates the crime of financing terrorism. Theevil conspiracy regulated in Article 5 of the Terrorism Financing Law is one of the conditions thatmust be fulfilled by criminals. In this study, the defendants in the decision of the East JakartaDistrict Court No. 398/Pid/Sus/2018/PN.Jkt.Tim were used as the object of research to assess howthe crime of financing terrorism to finance terrorism was applied and to assess the factorsconsidered by the judge. in applying the criteria for conspiracy in the financing of criminal acts ofterrorism. Through an inventory of sources from books and laws and regulations, this research wasconducted using a normative juridical approach. The defendant was charged with Article 4 jo.Article 5 of Law Number 9 of 2013 concerning Prevention and Eradication of Terrorism FinancingCrimes and Article 15 jo. Article 7 of Law Number 15 of 2003 concerning Criminal Acts ofTerrorism and sentenced to 4 years in prison. The activities of the accused, who have been provento be part of a conspiracy to finance terrorism, can be identified according to the qualifications ofthe articles charged by the public prosecutor. The decision was considered inappropriate inapplying the crime of conspiracy as in the judge's decision.